Rising above financial storms - Koay, Tan Chong (Kenance Sdn Bhd, 2015)
This book is about equity investing. It provides many gems of wisdom on how to be a successful investor, even amid financial crises. Here, author Dr Tan Chong Koay, founder of Pheim Malaysia and Pheim Singapore, sets out his investing philosophy, which is based on his many decades of investing in emerging as well as developed markets.